Mucosal incision-assisted biopsy versus endoscopic ultrasound-assisted tissue acquisition for subepithelial lesions: a systematic review and meta-analysis - Suprabhat Giri; Shivaraj Afzalpurkar; Sumaswi Angadi; Sridhar Sundaram (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Mucosal incision-assisted biopsy (MIAB) for tissue acquisition (TA) from subepithelial lesions (SELs) is emerging as an alternative to endoscopic ultrasound (EUS)-guided TA. Only a limited number of studies compared the diagnostic utility of MIAB and EUS for upper gastrointestinal (GI) SELs; therefore, we conducted this systematic review and meta-analysis. Methods A comprehensive literature search from January 2020 to January 2022 was performed to compare the diagnostic accuracy and safety of MIAB and EUS-guided TA for upper GI SELs. Results Seven studies were included in this meta-analysis. The pooled technical success rate (risk ratio [RR], 0.96; 95% confidence interval [CI], 0.89-1.04) and procedural time (mean difference=-4.53 seconds; 95% CI, -22.38 to 13.31] were comparable between both the groups. The overall chance of obtaining a positive diagnostic yield was lower with EUS than with MIAB for all lesions (RR, 0.83; 95% CI, 0.71-0.98) but comparable when using a fine-needle biopsy needle (RR, 0.93; 95% CI, 0.83-1.04). The positive diagnostic yield of MIAB was higher for lesions <20 mm (RR, 0.75; 95% CI, 0.63-0.89). Six studies reported no adverse events. Conclusions MIAB can be considered an effective alternative to EUS-guided TA for upper GI SELs without an increased risk of adverse events.